Influence of phosphorus compounds on the formation of ammonium ions by cells of nitrogen-fixing bacteria Аzotobacter chroococcum VKM V-1272 - Zvir, G.; Rizun, Н.; Hnatush, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
This article presents the results of investigation of the influence of inorganic compounds of phosphorus (potassium hydroortophosphate, sodium hydroorthophosphate) and phosphorus fertilizers (superphosphate, phosphorite flour) on the accumulation of biomass and the formation of ammonium ions by the cells of nitrogen-fixing bacteria А. chroococcum VKM V-1272. Sodium hydrophosphate, superphosphate and phosphorite flour were introduced into the culture medium (Ashby medium) instead of K2HPO4 at equimolar concentrations to the phosphate ion concentration in Ashby medium and at double concentration. It was established that Na2HPO4·12H2O, superphosphate and phosphorite flour at equimolar concentration stimulated the accumulation of biomass of A. chroococcum VKM V-1272, but at higher concentration they inhibited bacterial growth when compared to control. An increase of the concentration of Na2HPO4·12H2O and K2HPO4 in the culture medium there was inhibited not only the growth but also the formation of ammonium ions by A. chroococcum VKM V-1272 bacteria. Phosphate fertilizers at all concentrations inhibited the nitrogen fixation process. The effectiveness of the using of phosphorus compounds by bacteria А. chroococcum VKM V-1272 in the growth process has also been investigated. It has been established that soluble inorganic compounds (potassium hydroortophosphate, sodium hydroortophosphate) can be used by bacteria with different effectiveness as a source of phosphorus. In a medium with Na2НРО4·12H2O, К2НРО4 and superphosphate we observed a decrease of the concentration of phosphate ions that evidences that bacteria A. chroococcum VKM B-1272 use them during growth. Increasing of the concentration of phosphate ions in the medium with phosphorite flour indicates the ability of bacteria to phosphate mobilization. So the accumulation of biomass and the formation of ammonium ions by nitrogen-fixing bacteria A. chroococcum VKM B-1272 depended on the nature and concentration of the phosphorus source in the growth medium. Therefore, further studies of the influence of phosphorus nutrition on the physiological and biochemical properties of nitrogen-fixing bacteria will allow to evaluate the sensitivity of A. chroococcum VKM B-1272 to the action of inorganic pollutants and to show the importance of rational use of phosphorus fertilizers in agriculture.